Kinematic response functions and dynamic stiffnesses of bridge embankments. - Zhang, Jian (Earthquake engineering & structural dynamics.)
Recognizing that soil structure interaction affects appreciably the earthquake response of highway overcrossings, this paper compares approximate analytical solutions and finite element results to conclude on a simple procedure that allows for the estimation of the kinematic response functions and dynamic stiffnesses of approach embankments. It is shown that the shear wedge model yields realistic estimates for the amplification functions of typical embankments and reveals the appropriate levels of dynamic strains which are subsequently used to estimate the stiffness and damping coefficients of embankments. The shear wedge model is extended to a two dimensional model in order to calculate the transverse static stiffness of an approach embankment loaded at one end. The formulation leads to a sound closed form expression for the critical length, Lc, that is the ratio of the transverse static stiffness of an approach embankment and the transverse static stiffness of a unit width wedge. It is shown through two case studies that the transverse dynamic stiffness ('spring' and 'dashpot') of the approach embankment can be estimated with confidence by multiplying the dynamic stiffness of the unit width wedge with the critical length, Lc. The paper concludes that the values obtained for the transverse kinematic response function and dynamic stiffness can also be used with confidence to represent the longitudinal kinematic response function and dynamic stiffness, respectively.